(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Background: Diabetic nephropathy (DN) is a leading cause of end-stage renal disease (ESRD) among type 2 diabetes mellitus (T2DM) patients. Understanding its prevalence and risk factors is crucial for early intervention and management. Objective: This systematic review synthesizes evidence from cross-sectional studies on the prevalence and associated risk factors of DN among T2DM patients in internal medicine outpatient clinics. Methods: A comprehensive search was conducted in PubMed, Scopus, Web of Science, and Google Scholar for relevant studies published up to March 202 Studies reporting prevalence and risk factors of DN in T2DM patients were included. Data were extracted and analyzed using a random-effects model. Results: The pooled prevalence of DN among T2DM patients was 39.1% (95% CI: 36.7–41.5%). Significant risk factors included longer diabetes duration (OR: 2.1, 95% CI: 1.8–2.5), poor glycemic control (HbA1c ≥7%) (OR: 3.2, 95% CI: 2.7–3.8), hypertension (OR: 3.1, 95% CI: 2.6–3.7), dyslipidemia (OR: 2.8, 95% CI: 2.3–3.4), obesity (OR: 2.4, 95% CI: 2–2.9), and smoking (OR: 1.8, 95% CI: 1.5–2.2). Conclusion: DN is highly prevalent among T2DM patients in outpatient settings, with modifiable risk factors playing a significant role. Early screening and targeted interventions are essential to reduce DN progression.